Dunbar syndrome: a rare presentation of abdominal angina treated by revascularization of the celiac artery by endovascular stenting - Shetty, Rakshith; Subramanyam, K.; Jacob, Chinthu Sara (International Journal of Research in Medical Sciences, 2018)
Median arcuate ligament syndrome (MALS) is a rare entity characterized by extrinsic compression of the celiac artery and symptoms of postprandial epigastric pain, nausea, vomiting, and weight loss mimicking mesenteric ischemia. The following case illustrates a rare cause of abdominal pain, where this young woman was found to have celiac trunk stenosis , secondary to compression of the trunk by the median arcuate ligament. She underwent a successful stenting to the ostial celiac trunk, thus reliving her symptomatically. Decompression of the celiac artery is the general approach. Usually post PTA, once revascularisation is achieved, 75% of the patients remain asymptomatic at follow up.